Effect of processing conditions on the fracture behavior of Al-5Zn1.5Mg-1.0Mn-0.35Cu alloy fabricated from recycled beverage cans (RBCs) for bumper beam applications - Kazeem, Abubakar; H. Rady, Mohammed; Badarulzaman, Nur Azam; Wan Ali, Wan Fahmin Faiz; Suhaimi, Mohd Azlan; Jikan, Suzi S.; Abd Rahim, Shayfull Zamree; Sharif, Safian (Weldpro Sales & Services S/B, 2021)
The literature is a deficit of the effect of fractographic and microstructural analyses on the yield strength (δ ) of experimental 7xxx alloy fabricated from Recycled Beverage Cans (RBCs). This paper aims at correlate between fractography, microstructures, chemical compositions, and δy with respect to heat treatment (HT) parameters. Both intergranular and intergranular fractures were found predominantly ductile with micro dimples. Prolonged ageing time increased the thickness of boundaries and precipitated free zones (PFZs). Micro-voids and flake-like patterns indicated the formation of secondary phases. Maximum δy of 129 MPa and elongation of 16.3 % were observed in an alloy annealed (o) at 413 °C, artificial aged (T6) at 145 °C, for 6 h. Thus, modifications of HT process has significantly influenced the δy and microstructure of the alloy fabricated from RBCs. Future studies should concentrate on investigating the effect of variations in the wt. % Zn on the mechanical properties.